Water filling of rapidly salted separated egg yolks: Characterization of water migration, aggregation behavior and protein structure - Yaotong Liu; Yujie Chi; Yuan Chi (Food Chemistry Advances, 2023)
Water filling occurs during the rapid salting of separated egg yolks. The purpose of this study was to investigate the changes in water migration, protein aggregation and structures of the separated egg yolks salted with 20% salt solution over 24 hours to understand the principles of this phenomenon. The results showed that water filling occurred within 12 h. The hardness of the salted egg yolk increased significantly within approximately 0−6 h and then decreased significantly. The springiness and cohesiveness of the egg yolk did not change significantly during salting. With the appearance of water filling, the T23, A23, soluble protein content, free sulfhydryl content, β-turns, α-helices and maximum fluorescence intensity (FImax) increased; the T22, A22, disulfide bonds, β-sheets, irregular curls, maximum emission wavelength (λmax) and average particle sizes decreased. This work showed that water filling enhanced the hydrogen bonding between proteins and water and inhibited protein aggregation.